Exploration of the differences in developer experience of an IoT low-code development platform between citizen developers and professional developers - Tuominen, Niko (2023)
Low- and no-code development platforms are software platforms that enable the creation of applications through graphical user interfaces rather than through traditional programming. This enables software development for the so called ‘citizen developers’ – that is, people without a software developer background – and thereby helps answer the current shortage of highly skilled software developers. This thesis explores and compares through nine qualitative interviews the differences in the perception of the developer experience of an IoT low-code development platform held by both citizen developers as well as users with a professional software developer background. Based on an analysis of the interviews, it was discovered that while there are similarities between the two groups’ experiences, there are also differences. The three main differences between the two user groups’ experiences were how the users’ sense of the platform’s ease of use developed over time, how smooth or rough the use felt, and how the platform was experienced in terms of limiting or enabling creativity. The causes for negative developer experience are evaluated and several feature improvement ideas for the case platform were formulated based on the interviews.